Body image among elite rugby union players - Gibson, C.; Hindle, C.; McLay-Cooke, R.; Slater, J.; Brown, R.; Smith, B.; Baker, D.; Healey, P.; Black, K. (The Journal of Strength and Conditioning Research, 2019)
There is limited information on the risk of eating disorders (EDs) and body image of elite male athletes. However, research studies suggest that there are some athletes who have poor body image and they may be at increased risk of developing EDs. Therefore, the current study investigated risk of EDs, body image, and the relationship with age, in elite rugby union players during their preseason training period. This cross-sectional study was undertaken at the start of the preseason among elite rugby union players in New Zealand. Twenty-six professional rugby union players completed a 49-item questionnaire on body image and disordered eating. A "body image score" was calculated from questionnaire subscales including "drive for thinness," "bulimia," and "body dissatisfaction," with total scores above 20 indicative of poor body image. Body image scores varied from 8 to 39 out of a possible 0-100. Disordered eating behaviors were reported, including binge eating at least once a week (15%, n = 4/26), pathogenic weight control use (4%, n = 1/26), and avoidance of certain foods (77%, n = 20/26). There was a statistically significant inverse association between the bulimia subscale and age (p = 0.034). At the start of the preseason training period, many elite rugby union players experience disturbances in body image. The prevalence of disordered eating behaviors is of concern, and needs to be minimized due to the negative impact on health and performance. A focus on assessment and education of younger male rugby players may be required to reduce disordered eating patterns.